Paclitaxel-loaded multifunctional nanoparticles for the targeted treatment of glioblastoma. (3rd July 2019) - Ganipineni, Lakshmi Pallavi; Ucakar, Bernard; Joudiou, Nicolas; Riva, Raphaël; Jérôme, Christine; Gallez, Bernard; Danhier, Fabienne; Préat, Véronique
Abstract: Introduction: We hypothesised that the active targeting of αvβ3 integrin overexpressed in neoangiogenic blood vessels and glioblastoma (GBM) cells combined with magnetic targeting of paclitaxel- and SPIO-loaded PLGA-based nanoparticles could improve accumulation of nanoparticles in the tumour and therefore improve the treatment of GBM. Methods: PTX/SPIO PLGA nanoparticles with or without RGD-grafting were characterised. Their in vitro cellular uptake and cytotoxicity was evaluated by fluorospectroscopy and MTT assay. In vivo safety and anti-tumour efficacy of different targeting strategies were evaluated in orthotopic U87MG tumour model over multiple intravenous injections. Results: The nanoparticles of 250 nm were negatively charged. RGD targeted nanoparticles showed a specific and higher cellular uptake than untargeted nanoparticles by activated U87MG and HUVEC cells. In vitro IC50 of PTX after 48 h was ∼1 ng/mL for all the PTX-loaded nanoparticles. The median survival time of the mice treated with magnetic targeted nanoparticles was higher than the control (saline) mice or mice treated with other evaluated strategies. The 6 doses of PTX did not induce any detectable toxic effects on liver, kidney and heart when compared to Taxol. Conclusion: The magnetic targeting strategy resulted in a better therapeutic effect than the other targeting strategies (passive, active).